Aplikasi Orai: Pemanfaatan Media Pembelajaran Alternatif Guna Melatih Kelancaran dan Kepercayaan Diri Public speaking Mahasiswa - Sifa Yunita Sari; Agus Purnomo Ahmad Putikadyanto (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2023)
This research is motivated by the importance of public speaking for students, but the lack of fluency in public speaking for students. This is something that needs a solution. The aim of this research is to describe the use of the Orai application as an alternative learning media to train students’ public speaking fluency and confidence. This research uses descriptive qualitative methods. Data collection techniques in this research are observation, interviews and documentation. The results of this research are in the form of using the Orai application as an alternative learning media to train students’ public speaking fluency and confidence in several stages. These stages include; downloading, using and describing the application.